2006
DOI: 10.2460/javma.229.6.984
|View full text |Cite
|
Sign up to set email alerts
|

Toggle rod stabilization for treatment of hip joint luxation in dogs: 62 cases (2000–2005)

Abstract: Results of the present study suggest that toggle rod stabilization is an effective treatment for hip joint luxation in dogs. However, complications, particularly reluxation, were common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
103
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(118 citation statements)
references
References 17 publications
11
103
2
2
Order By: Relevance
“…Re‐luxation rates with toggle rod or related techniques have been reported and vary from 11%‐25% . Rapid return to weight bearing without the requirement for application of an Ehmer sling has been reported in multiple publications and can be especially important for patients with multitrauma or other orthopedic conditions, which are relatively common . Use of polyblend suture materials with extremely high tensile strength and load to failure is believed to be advantageous, but no biomechanical studies comparing their properties with respect to this application have been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Re‐luxation rates with toggle rod or related techniques have been reported and vary from 11%‐25% . Rapid return to weight bearing without the requirement for application of an Ehmer sling has been reported in multiple publications and can be especially important for patients with multitrauma or other orthopedic conditions, which are relatively common . Use of polyblend suture materials with extremely high tensile strength and load to failure is believed to be advantageous, but no biomechanical studies comparing their properties with respect to this application have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies comparing the biomechanical properties of these materials when used in various constructs to treat cruciate ligament disease are thought to be valid with respect to this technique . Obvious disadvantages of an open approach to toggle rod fixation are the associated surgical trauma and the potential for associated complications such as dehiscence, seroma formation, sciatic damage, and incisional infections, all of which have been reported …”
Section: Discussionmentioning
confidence: 99%
“…In another study which compared toggle rod and suture anchor, it was reported that toggle rod constructs failed primarily by breakage of the suture at the rod eyelet and suture anchor constructs failed when the anchors pulled through the medial acetabular wall [17] . In two different studies which used toggle rod with 62 dogs and 13 dogs, reluxation rates were declared as 11% [18] and 23% [33] , respectively. Besides, intraarticular stabilization methods may cause articular damage and subsequent arthrosis [30] .…”
Section: Discussionmentioning
confidence: 99%
“…The luxation should be treated surgically; if there are complications such as hip dysplasia existence prior to trauma, femoral and/or acetabular avulsion fractures, intra articular fractures, arthrosis and conditions such as multiple orthopedic injuries or chronic luxation, closed reduction failure and extreme instability after reduction [5,8,12,13] . Techniques which are used for the surgical treatment of coxofemoral luxations can be categorized as extracapsular such as suture of a joint capsule (capsulorrhaphy) [3,5,12] , synthetic capsule technique [2,3,6,14] , transposition of the greater trochanter [2,5,6,12] , triple pelvic osteotomy [2,8] and intra capsular techniques such as Modified Knowles Toggle pin fixation [3,6,8,15,16] , Toggle rod stabilization [17,18] , trans acetabular pinning [2,6,19] transposition of the sacrotuberous ligament [20,21] . Additionally, flexible external fixation [8] , total hip replacement [22][23][24] and femoral head and neck osteotomy [2,25,26] can be also applied for the treatment of hip luxation.…”
Section: Introductionmentioning
confidence: 99%
“…The open reduction included a capsulorrhaphy, which is a technique that has already been used in conjunction with other techniques in domestic animals (DEMKO et al, 2006;VENTURINI et al, 2010). Transarticular pinning was successful, even though it is indicated for recurrent luxation or in cases in which more conservative methods cannot be used (BENNETT & DUFF, 1980); the use of a toggle pin would have been another alternative and has been used successfully in the treatment of caudoventral hip luxations in small animals (ÇETINKAYA & OLCAY, 2010).…”
mentioning
confidence: 99%